Answer:
- h(x) = -2x^2 -x +3
- Reservoir A releases the same amount of water as Reservoir B over 1 week
Step-by-step explanation:
<u>Given</u>:
f(x) = x^2 -7x +5
g(x) = 3x^2 -6x +2
h(x) = f(x) -g(x)
<u>Find</u>:
h(x)
h(1)
<u>Solution</u>:
The expression for h(x) is found by evaluating its definition:
h(x) = (x^2 -7x +5) -(3x^2 -6x +2)
h(x) = x^2(1 -3) +x(-7 -(-6)) +(5 -2)
h(x) = -2x^2 -x +3
Then h(1) is found by substituting 1 for x:
h(1) = -2(1^2) -(1) +3 = -2 -1 +3
h(1) = 0 . . . . difference in release amounts after 1 week is 0
The true statements are ...
- h(x) = -2x^2 -x +3
- Reservoir A releases the same amount of water as Reservoir B over 1 week
Step-by-step explanation:
Hypotenuse : Opposite the right angle.
Opposite : Opposite the angle.
Adjacent : the last side left.
Your formulas.
Soh Cah Toa (Sin Cos Tan)
You'll be using Cos (Cah) because hypotenuse and adjacent are the only sides with something in it.
You rearranged formula :
Side length × Cos (Angle) = your answer to x
Answer: The root of this function would be (7,0)
Answer: 67.2°
Step-by-step explanation:
To find angle C, we have to use cosine rule. Therefore,
12² = 8² + 10² - 2 × 8 × 10 × cosC
C = 82.8°
The bearing of A from C will be
= 150° - 82.8°
= 67.2°.
Answer:
im dumb im sorry but u can look it up
Step-by-step explanation: